Self-powered finger motion-sensing structural color display enabled by block copolymer photonic crystal. (February 2022) - Kim, Taebin; Lee, Jae Won; Park, Chanho; Lee, Kyuho; Lee, Chang Eun; Lee, Seokyeong; Kim, Yeonji; Kim, Sohee; Jeon, Seungbae; Ryu, Du Yeol; Koh, Won-Gun; Park, Cheolmin
Abstract: Self-powered user-interactive displays that facilitate the visualization of human information acquired by sensors are of great interest in emerging human–machine interface technology with efficient energy consumption. Herein, a self-powered motion-sensing display capable of simultaneously detecting and visualizing finger motions is presented. Our device is based on a one-dimensional photonic crystal of an interpenetrated hydrogel network block copolymer (IHN-BCP) consisting of alternating water-absorbable and non-absorbable lamellae. Triboelectrification is achieved as a function of relative humidity from 30% to 80%. The direct visualization of the humidity is also achieved through the humidity-dependent structural color of the photonic crystal in the full visible range. Furthermore, the humidity-responsive triboelectrification and structural color of our IHN-BCP photonic crystal facilitates the development of a self-powered finger motion-sensing display where diverse gestures of a finger with natural humidity are quantitatively recognized, such as vertical and sliding motion of the finger with simultaneous visualization of the motions in both contact and non-contact modes. Graphical Abstract: Self-powered finger motion-sensing display capable of simultaneously detecting and visualizing finger motions is developed, based on the one-dimensional photonic crystal of a self-assembled block copolymer. The humidity-responsive triboelectrification and structural color of our photonic crystal allows the quantitative sensing and visualization of diverse gestures of a finger with natural humidity. ga1 Highlights: We demonstrate self-powered finger motion-sensing display based on self-assembled block copolymer photonic crystal We utilize humidity-dependent triboelectrification and structural color of the photonic crystal in finger motion. Self-powered triboelectric sensing is accomplished with simultaneous evolution of structural color in various finger motions.